Marketing and Management Analysis of Dark Tourism Product - Pavel Tvrzník; Tomáš Jeřábek; Zdeněk Málek; Katarína Mrkvová (Communications of International Proceedings, 2021)
Tourism is one of the most developing economic sectors one of its developing forms being the dark tourism, which, thanks to its development, can create a motivating element in the possible choice of destination. The aim of this paper is the marketing and management analysis of the memorial and museum of the internment camp in Svatobořice-Mistřín. Based on the marketing analysis in terms of current marketing activities, we propose further steps in the conclusions that can help successfully develop the attendance of the chosen monument and thus contribute to the development of tourism in the selected location. The conclusions summarize the results of the analysis and generalize them for practical application in dark tourism. The selected conclusions may be generally applicable in order to increase the tourism of the area with a minimum of negative impacts, which may be an accompanying phenomenon of increasing tourism.
Keywords: Dark Tourism; Marketing Analysis; Marketing Recommendations; Strategies For Further Development